MANAGEMENT AND CHALLENGES OF THE MOUNTAIN PINE BEETLE INFESTATION IN BRITISH COLUMBIA - Ritchie, Chris (Lakehead University, 2008)
Central British Columbia is currently subject to the largest outbreak of mountain pine beetle (Dendroctonus ponderosa) ever recorded in British Columbia. The massive expansion of this natural disturbance agent is a result of both natural and human-associated influences including milder winter weather and fire suppression policy. Resource managers are grappling with a response to the infestation that considers economic, social, and ecological factors. In British Columbia the response has moved from a control or sanitation phase, to an economic recovery or salvage phase. The condition of the landscape resulting from the insect and the management associated with each phase will impact wildlife populations. Distribution and abundance of certain species will either increase or decline in response to changes in the forest vegetation and hydrologic regime. Caribou (Rangifer tarandus caribou), fisher (Martes pennanti), marten (Martes americana), woodpeckers, and pygmy nuthatches (Sitta pygmaea) are considered species with high sensitivity to mortality of pine trees that will adversely affect their forage, cover, and nesting/denning habitat. Moose (Alces alces) will probably benefit in the short-term from increased forage resources, but may decline long-term from intensive forest management to recover mature forest stands. The impact of larger and more dispersed moose and wolf (Canis lupus) populations could harm the recovery and stability of threatened caribou populations in British Columbia.